Fate of nitrogen in a tropical peat soil treated with clinoptilolite zeolite - Krishnan, Kavinraj; Ahmed, Osumanu Haruna; Omar, Latifah; Ali, Maru; Chowdhury, Ahmed Jalal Khan; Musah, Adiza Alhassan (Desalination Publications, 2023)
Crop productivity on tropical peat soils is poor partly because of their nutrient deficiency and the acidic nature of tropical peat soils. Ammonium (NH4+) and nitrate (NO3–) ions are commonly leached from tropical peat soils principally because of high rainfall and lack of clay to retain these nutrients. Leaching of these ions into water bodies causes water pollution through eutrophication which has been implicated in disrupting productive aquatic life. To reverse this act of environmental quality degradation, clinop-tilolite zeolite (CZ) could be used to retain nutrients including NH4 + – and NO3 in tropical peat soils for crop use because of the alkalinity and high affinity of CZ for retention of macronutrients. Moreover, this approach could be used as an innovative and sustainable alternative for high use of lime (CaCO3) because of the liming effect of CZ. However, information on using CZ on tropical peat soils is scarcely explored. Thus, CZ was tested in a leaching study to determine its effects on soil total nitrogen (N), exchangeable ammonium, and nitrate retention in a tropical peat soil. Treatments evaluated were: (i) soil only, (ii) nitrogen, phosphorus, potassium (NPK) fertilizer alone, and (iii) combination of different amounts of clinoptilolite zeolite (25%, 50%, 75%, and 100%) and different amounts of NPK fertilizer (50%, 75%, and 100%). The peat soils with CZ improved soil pH, exchangeable NH4+, and available NO3– . + – + The mixture of CZ and NPK fertilizer reduced NH4 and NO3 loss because CZ has high affinity for NH4 – whereas NO3 was absorbed into the channels of CZ. Co-application of 100% CZ with 100%, 75%, and 50% NPK fertilizer, together with 75%, 50%, and 25% CZ with 100% fertilizer increased total N of the peat soil. Ability of CZ to buffer the soil pH reduces the need for liming. This alternative way of retaining N in tropical peat soils is practical and a sustainable approach for improving peat soil productivity.